SEKALA USAHA KLANTING DAN KONTRIBUSINYA TERHADAP PENDAPATAN KELUARGA DI DESA SIDORAHAYU KECAMATAN BELITANG OKU TIMUR - Catur Giyanto (Sekolah Tinggi Ilmu Pertanian (STIPER) Belitang, 2016)
The purpose of this research were to: 1. To determine the scale of industrial enterprises in the village klanting sidorahayu Belitang District of East OKU. 2. To determine the production costs and revenue from product diversification klanting Village Belitang sidorahayu District of East OKU. 3. To find out how much industry revenue klanting contribution to the family income in the village sidorahayu Belitang District of East OKU. This research has been conducted in the village sidorahayu Belitang District of East OKU. The location determination is done deliberately, with the consideration that in the village there is a household scale industrial enterprises that process cassava into klanting. The execution of the research carried out on the Moon April-May 2014. The method used in this research is survey method with sampling techniques. This study found that the scale of effort klanting Village sidorahayu District of Belitang East OKU classified as micro, because the cost of business production average - average of Rp 134,792,887 per year, Revenue Average - Average Rp 206,181,818 per year and the average - average revenue of Rp 71,388,931 per year, The production cost of an average effort klanting Rp 374.425 / Pp, average receipts of Rp 572 727 / Pp and average revenue - average of Rp 198.303 / Pp and business contribution klanting to the family income in the village sidorahayu District of Belitang East OKU by 80%.